Hybrid Constitutions : Challenging Legacies of Law, Privilege, and Culture in Colonial America - Hsueh, Vicki, 1973- (Book collections on Project MUSE., 2010)
Study of three proprietary colonies--Maryland, Carolina, and Pennsylvania--that emphasizes the uneven, local, and contingent aspects of the development of American constitutionalism.